The Effect of Interactive Audio-Visual Learning Media on Elementary School Students' Thematic Learning Outcomes - Christine Wulandari Suryaningrum; Moch. Fauzi; Neti Desrianti; Asmedy Asmedy (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2026)
The continued dominance of lecture-based thematic instruction in elementary classrooms may limit students’ cognitive engagement and learning outcomes, particularly when abstract concepts are delivered mainly through verbal explanation. This study aimed to examine the effect of interactive audio-visual media on fifth-grade students’ learning outcomes in thematic learning. Interactive audio-visual media in this study refers to learning media that integrate narration, images, text, animation, and student response activities. A quantitative approach was employed using a quasi-experimental method with a nonequivalent control group design. The participants were 36 fifth-grade students of SDN 07 Dompu, consisting of 18 students in the experimental group and 18 students in the control group. Data were collected using pretest and posttest learning achievement tests and analyzed through descriptive statistics, normality and homogeneity tests, and an independent samples t-test at the 0.05 significance level. The results showed that the experimental group achieved a higher posttest mean score (M = 82.22) than the control group (M = 71.39). The learning gain in the experimental group was also higher (28.61 points) than in the control group (13.06 points). The t-test result indicated a significant difference between groups, t(34) = 3.672, p = .001. These findings suggest that interactive audio-visual media can improve students’ thematic learning outcomes by supporting concept visualization, multimodal information processing, and active participation. However, the findings should be interpreted within the limited sample and school context. This study implies that elementary teachers should design audio-visual media not merely as presentation tools, but as interactive learning resources aligned with learning objectives and assessment indicators.